Pengaruh Kualitas Produk, Atribut Produk dan Harga Terhadap Keputusan Pembelian Produk Smart TV Merek Samsung Di UFO Elektronik Teuku Umar Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Product quality is one of the key elements in marketing strategy, involving consumers' assessment of a product's ability to fulfill its value and function. In addition to product quality, other factors that influence purchasing decisions include product attributes and price. Good product attributes can provide information, features, and designs that meet consumer expectations, while an appropriate price encourages consumers in making purchasing decisions. The purpose of this study is to determine the influence of product quality, product attributes, and price on purchasing decisions for Samsung smart tv products at UFO Elektronik Teuku Umar Denpasar. This research was conducted at the UFO Elektronik store on Teuku Umar Street, Denpasar, with a sample size of 95 consumers, using a purposive sampling method. Data collection was carried out through a survey approach, with research instruments including literature review, interviews, and questionnaires. The collected data were then analyzed using multiple linear regression analysis. The results of the study show that product quality, product attributes, and price both simultaneously and partially have a positive and significant effect on purchasing decisions for Samsung smart tv products at UFO Elektronik Teuku Umar Denpasar. The implication of this study is that companies should improve product quality, pay attention to product attributes, and set appropriate prices to encourage increased consumer purchasing decisions.